2006
DOI: 10.1159/000093099
|View full text |Cite
|
Sign up to set email alerts
|

Association of μ-Opioid Receptor Gene Polymorphism A118G with Alcohol Dependence in a Japanese Population

Abstract: Ethanol is considered to activate the brain reward system by increasing the release of an endogenous opioid receptor ligand, β-endorphin. The polymorphism A118G in the µ-opioid receptor gene (OPRM1) causes the amino acid change Asn40Asp and has been reported to affect the affinity of the ligand for the receptor. The association of this polymorphism with the vulnerability to alcohol dependence has been studied in many populations, but not yet in Japanese people. In the present study, we compared the frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…In African-Americans, A118G was not associated with dependence (although the 3% frequency of the G allele in this ethnic group substantially comprises power), while women with the T/T genotype at the rs1799972 polymorphism were found to consume more alcohol [89, 93]. Among Asian populations, the minor allele of A118G was associated with alcoholism in Indian and Japanese cohorts [51, 94]. This association was not observed in studies of Korean or Taiwanese patients, although the G allele did correlate with an increase in the number of drinking days over the course of the study [95-97].…”
Section: The μ-Opioid Receptormentioning
confidence: 99%
“…In African-Americans, A118G was not associated with dependence (although the 3% frequency of the G allele in this ethnic group substantially comprises power), while women with the T/T genotype at the rs1799972 polymorphism were found to consume more alcohol [89, 93]. Among Asian populations, the minor allele of A118G was associated with alcoholism in Indian and Japanese cohorts [51, 94]. This association was not observed in studies of Korean or Taiwanese patients, although the G allele did correlate with an increase in the number of drinking days over the course of the study [95-97].…”
Section: The μ-Opioid Receptormentioning
confidence: 99%
“…The G-allele (OPRM1*G) of rs1799971 has been reported to be significantly associated with alcohol cravings and dependence in Asians. 9,10 Although the molecular mechanism of how the OPRM1 SNP influences drinking behavior remains to be elucidated, the multiplexed SNP genotyping of the OPRM1 in addition to the ADH1B and ALDH2 is highly likely to be useful to predict the risk of alcoholism. To our knowledge, this is the first report of a rapid and cost-effective method for AS-PCR-mediated SNP genotyping ADH1B and ALDH2 genes (as well as the OPRM1 gene) by utilizing two-step PCR thermal cycles requiring 50 min or less.…”
Section: Introductionmentioning
confidence: 99%
“…Four clinical studies conducted on East Asians showed that subjects homozygous for G118 needed higher morphine doses to attain adequate pain control following surgery than those of homozygous for A118 [6-9]. In addition, subjects of G/G or A/G genotype have better treatment outcomes for nicotine and alcohol abuse [10-12] and higher propensity for drug addiction [13-16][reviewed in [17]].…”
Section: Introductionmentioning
confidence: 99%